Individual privacy and computer-based human resource information systems - Taylor, G. Stephen (Journal of business ethics, 1989)
The proliferation of computers in the business realm may lead to ethical problems between individual and societal rights, and the organization's need to control costs. In an attempt to explore the causes of this potential conflict, this study examined the varying levels of sensitivity 223 respondents assigned to different types of information typically stored in computer-based human resource information systems. It was found that information most directly related to the job — pay rate, fringe benefits, educational history — was considered to be the most sensitive. Participants, however, were more concerned about certain types of individuals/groups accessing these systems than about the kinds of information contained in them. Implications of these findings are discussed.